2010
DOI: 10.1152/ajpheart.01137.2009
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of fibrosis-related arrhythmias by chronic renin-angiotensin-aldosterone system inhibitors in an aged mouse model

Abstract: Myocardial fibrosis increases arrhythmia vulnerability of the diseased heart. The renin-angiotensin-aldosterone system (RAAS) governs myocardial collagen synthesis. We hypothesized that reducing cardiac fibrosis by chronic RAAS inhibition would result in reduced arrhythmia vulnerability of the senescent mouse heart. Wild-type mice (52 wk old) were treated for 36 wk: 1) untreated control (C); 2) eplerenone (E); 3) losartan (L); and 4) cotreatment with eplerenone and losartan (EL). Ventricular epicardial activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 28 publications
2
55
0
1
Order By: Relevance
“…4,5 Animal studies have shown that chronic aldosterone-overload induces structural and electrical remodelling of the myocardium increasing the risk for malignant ventricular arrhythmia 24 and the use of AA attenuated electrical remodelling and suppressed the inducibility of ventricular arrhythmia. 9,25,26 The use of AA causes a delay or reversal of myocardial fibrosis as noted by a decreased turnover of extracellular markers in the treatment arm of RALES trial. 27 Spironolactone has also been shown to reduce plasma levels of metalloproteinases in ischaemic HF indicating its role in reversing collagen dysregulation that plays a role in cardiac remodelling.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Animal studies have shown that chronic aldosterone-overload induces structural and electrical remodelling of the myocardium increasing the risk for malignant ventricular arrhythmia 24 and the use of AA attenuated electrical remodelling and suppressed the inducibility of ventricular arrhythmia. 9,25,26 The use of AA causes a delay or reversal of myocardial fibrosis as noted by a decreased turnover of extracellular markers in the treatment arm of RALES trial. 27 Spironolactone has also been shown to reduce plasma levels of metalloproteinases in ischaemic HF indicating its role in reversing collagen dysregulation that plays a role in cardiac remodelling.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, spironolactone treatment prevents gap junction remodeling and restores the decreased transverse conduction velocity in a thoracic aortic constriction model (Qu et al, 2009). Likewise, eplerenone reduces fibrosis-related arrhythmias in aged mice (Stein et al, 2010). Both spironolactone and eplerenone reduce the prolongation of QT intervals and diminishes the occurrence of ventricular premature beats or nonsustained ventricular tachycardia in aldosterone-infused rats (Dartsch et al, 2013).…”
Section: B Mineralocorticoid Receptor and Electrophysiological Disormentioning
confidence: 99%
“…Direct evidence for the role of Ang II in cardiac aging came in 2007, when Basso, et al reported that inhibition of Ang II signaling by either angiotensin converting enzyme inhibitor enalapril or angiotensin receptor type I inhibitor losartan extended the lifespan of normal male Wistar rats and slowed the onset of agerelated cardiovascular pathologies (22). These drugs have also been shown to reduce myocardial fibrosis and fibrosis-related arrhythmias in aged mice (304). This was confirmed by a study which demonstrated that mice with disruption of angiotensin receptor type I prolong mouse survival (29).…”
Section: Fig 7 Mitochondrial Oxidative Damage In Cardiac Aging (A)mentioning
confidence: 99%